Pengaruh Kemasan Terhadap Minat Beli Masyarakat Dengan Kualitas Sebagai Variabel Mediasi Pada Produk “Legit” - Billy Ivanko dan Hetty Karunia Tunjungsari (Universitas Tarumanagara, 2019)
The purpose of this research was to analyze the effect of packaging toward purchase intention with quality of the product as a mediation variable for Micro, Small, and Medium Scale Business “Legit” Product. This research used descriptive quantitative methods. The method of data collection were primary and secondary data. The population of this research is the entire Indonesia population of 2016 (257.912.349 peoples). This study used non-probability sampling technique by taking purposive sampling. This study used simple linear regression and multiple linear regression with instrument test, a classic assumption (normality, multicollinearity, and heteroscedasticity), model test (adjusted R2, T test and F test), Causal Steps and Bobel Test to checked the validity of the hypothesis. Based on the results of the study, it was found that the packaging has a significant effect on the purchase intention of the Legit’s product, the packaging has a significant effect towards the quality of the Legit’s product and the packaging has a significant effect towards the purchase intention of the Legit’s product with the quality of the product as a mediated variable.